Numerical investigation of fire spread, evacuation and hazard assessment in an offshore petroleum platform by using cfd simulation - Nasif M.S.; Ahmed M.A.M.; Hasnain S.A.; Kamaruzaman A.; Ismail F.B. (Asian Research Publishing Network, 2023)
In case of fire in an offshore oil platform the safe evacuation of people from the hazardous location is of great concern. This study investigates the safety evacuation path provided in petroleum offshore platform for occupant evacuation under fire conditions by using FDS - Evac CFD software. It was found that the evacuation time obtained from the CFD - evacuation simulation results is within the accuracy of around 97% as compared with the standard evacuation time used in an offshore platform. Results also showed that seventy one people at ground deck will be exposed to the high temperature of 300 C, which can cause 3rd degree burn or death. Evacuation of occupants from the upper decks (2nd, 3rd and 4th) is found to be safe. Based on the results obtained, it is recommended to install a fire resistant wall at the evacuation egress route in order to prevent occupants from being exposed to high temperature during evacuation. 2006-2017 Asian Research Publishing Network (ARPN).